A review of the genus Angilia Stål, 1865 (Hemiptera: Heteroptera: Veliidae): New species, new synonyms, checklist, and key to species - Higor D. D. Rodrigues; Robert W. Sites; Felipe F. F. Moreira (PLoS ONE, 2025)
Angilia Stål, 1865 is one of three genera of the subfamily Veliinae (Hemiptera: Heteroptera: Veliidae) from the Eastern Hemisphere and is distributed in sub-Saharan Africa, Madagascar, and Southeast Asia. Currently, 23 species and five subspecies are known and the genus is divided into two subgenera: Angilia (Angilia) Stål, 1865 and A. (Adriennella) Poisson, 1942. We present here the descriptions of two new species from Africa: A. (An.) morogoro n. sp., from Tanzania, and A. (Ad.) igniventris n. sp., from Madagascar. In addition, we propose A. (An.) albidotincta ugandensis Poisson, 1955 as a junior subjective synonym of A. (An.) a. albidotincta (Stål, 1855); A. (An.) kaokoveldi Poisson, 1958a as a junior objective synonym and junior homonym of A. (An.) kaokoveldi Poisson, 1957; A. (An.) albidotincta kaokoveldi Poisson, 1958b as a junior subjective synonym and junior homonym of A. (An.) kaokoveldi Poisson, 1957; A. (An.) collarti Poisson, 1958a as a junior objective synonym and junior homonym of A. (An.) collarti Poisson, 1957; transfer Angilia perplexa Poisson, 1942 from the subgenus Adriennella to Angilia s. str.; and provide morphological notes and illustrations for the following species: A. (An.) aeterna Hoberlandt, 1946, A. (An.) albidotincta, A. (An.) ambakakae Poisson, 1952, A. (An.) congoensis Poisson, 1950, A. (An.) kaokoveldi, A. (An.) rhodesiensis Poisson, 1955, A. (Ad.) anderseni Zettel & Hecher, 1998, A. (Ad.) bertrandi Poisson, 1963, A. (Ad.) bispinosa Andersen, 1981, A. (Ad.) conradsi Poisson, 1950, A. (Ad.) orientalis Andersen, 1981, A. (Ad.) philippiensis Drake & Hoberlandt, 1953, and A. (Ad.) schoutedeni schoutedeni Poisson, 1942. We also designate lectotypes for three species and present a checklist and key to the species.